Evaluation of intranasal TLR2/6 agonist INNA-051: safety, tolerability and proof of pharmacology - Francesca A. Mercuri; Scott White; Hayley A. McQuilten; Charlotte Lemech; Stephan Mynhardt; Rana Hari; Ping Zhang; Nicole Kruger; Grant McLachlan; Bruce E. Miller; Nicholas P. West; Ruth Tal-Singer; et al. (ERJ Open Research)
Background Local priming of the innate immune system with a Toll-like receptor (TLR)2/6 agonist may reduce morbidity and mortality associated with viral respiratory tract infections, particularly for the elderly and those with chronic diseases. The objectives of the present study were to understand the potential of prophylactic treatment with a TLR2/6 agonist as an enhancer of innate immunity pathways leading to accelerated respiratory virus clearance from the upper airways. Methods Two randomised, double-blind, placebo-controlled clinical trials were conducted in healthy adult participants. The first dose-escalation study assessed safety, tolerability and mechanistic biomarkers following single and repeated intranasal administrations of INNA-051. The second was an influenza A viral challenge study assessing the impact of treatment on host defence biomarkers and viral load. Results INNA-051 was well tolerated in both studies, with no dose-limiting toxicities identified. Mechanistic biomarkers assessed in both studies demonstrated the expected engagement of pharmacology, including innate immune pathways. There were lower than anticipated rates of infection. Post hoc analysis conducted in laboratory-confirmed infected participants with low or no antibody titre against the challenge virus showed INNA-051 treatment led to a significantly shorter duration of infection and increased expression of genes and pathways associated with host defence responses against influenza. Conclusions The safety and pharmacology profile of INNA-051 confirms preclinical studies. INNA-051 increased expression of genes and pathways associated with host defence responses against influenza and was associated with a shorter duration of infection. These studies support further clinical assessment in the context of natural viral respiratory tract infections in individuals at increased risk of severe illness.